A preliminary study on pressure‐plate evaluation of forelimb toe–heel and mediolateral hoof balance on a hard vs. a soft surface in sound ponies at the walk and trot. (12th January 2014) - Oosterlinck, M.; Royaux, E.; Back, W.; Pille, F.
Summary: Reasons for performing study: Thus far, pressure‐plate analysis has been limited to measurements on a hard surface, whereas equine athletes routinely perform on a deformable substrate. Objectives: To explore pressure‐plate analysis on arena footing. Study design: Nonrandomised crossover study using noninvasive techniques. Methods: Five sound, unshod ponies were walked and trotted over a pressure plate in 2 different conditions. In the first session, the plate was covered with only a 5 mm rubber mat, and in the second session, with an additional 50 mm layer of sand and synthetic fibres. Limb loading and timing variables (peak vertical force, vertical impulse, peak vertical pressure, hoof contact area and stance phase duration) were obtained. Toe–heel and mediolateral hoof balance of the vertical force were calculated throughout stance (126 Hz). Results: Peak vertical force, vertical impulse, peak vertical pressure and stance phase duration were decreased on the soft substrate, while hoof contact area increased. At impact, there was more even load distribution between the toe and heel region on the soft vs. hard surface. At mid‐stance, there was more loading of the toe region on the soft compared with the hard surface. At impact, there was more even load distribution between lateral and medial on the soft vs. hard surface at walk, but not at trot. Conclusions: Comparison of observed vs. expected impulse indicated that the main factor involved in the lower loading on the soft surface is the dampening effect of the soft substrate, although definitive conclusions require concurrent force‐plate analysis. The pressure plate permitted quantitative evaluation of hoof balance of the vertical force on a deformable surface at the walk and trot and proved that there is more even load distribution on arena footing.